The Development of E-Commerce in Indonesia: Impact on MSMEs and Challenges of Digital Transactions - Putri Yasmin Ananda; Rizka Nabila Daulay; Sabathya Candy Br Nababan; Sri Wahyuni Br Silalahi; Dewi Urip Wahyuni (Perkumpulan Konsultan Manajemen Pendidikan Indonesia (PKMPI), 2025)
The development of E-Commerce in Indonesia in recent years has become one of the main factors in the change of the digital economy. Micro, Small, and Medium Enterprises (MSMEs), which serve as the backbone of the country’s economy, have gained significant opportunities through access to a wide market, improved operational efficiency, and ease in marketing and transactions. However, on the other hand, there are various challenges that must be faced, such as uneven digital literacy, logistics infrastructure that still needs improvement, issues of security and trust in digital transactions, as well as the complexity of regulations and taxation, along with competition from imported products and large platforms. This article aims to analyze how the development of electronic commerce has impacted MSMEs in Indonesia and to identify various key challenges in digital transactions that still hinder the optimization of its benefits